2017
DOI: 10.1101/137059
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Improved Split Fluorescent Proteins for Endogenous Protein Labeling

Abstract: Self-complementing split fluorescent proteins (FPs) have been widely used for protein labeling, visualization of subcellular protein localization, and detection of cell-cell contact.To expand this toolset, we have developed a screening strategy for the direct engineering of self-complementing split FPs. Via this strategy, we have generated a yellow-green split-mNeonGreen2 1-10/11 that improves the ratio of complemented signal to the background of FP 1-10 -expressing cells compared to the commonly used split GF… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
53
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 25 publications
(55 citation statements)
references
References 42 publications
2
53
0
Order By: Relevance
“…To create the NGFR-mNG2(11) WM989-A6-G3 cell line, we used the split mNeonGreen2(mNG2) system described in Ref. (Feng et al, 2017) . In brief, we first transduced WM989 A6-G3 with 10/11ths of mNG2, which is non-fluorescent without the remaining 1/11th of the protein.…”
Section: Methodsmentioning
confidence: 99%
“…To create the NGFR-mNG2(11) WM989-A6-G3 cell line, we used the split mNeonGreen2(mNG2) system described in Ref. (Feng et al, 2017) . In brief, we first transduced WM989 A6-G3 with 10/11ths of mNG2, which is non-fluorescent without the remaining 1/11th of the protein.…”
Section: Methodsmentioning
confidence: 99%
“…To uncover the connection between EML4-ALK granules and RAS activation, we created a library of gene-edited Beas2B cell lines by introducing a split mNeonGreen21-10/11 tag (mNG2) at the endogenous locus of canonical adaptor and effector proteins in the RTK/RAS/MAPK signaling pathway, including GRB2, GAB1, SOS1, RAS GTPases (H/N/K isoforms) and RAF (A/B/C isoforms) [21]. This suite of isogenic cell lines avoids potential biases that can arise when overexpressing labeled proteins or fixing and permeabilizing cells for immunofluorescence.…”
Section: Main Text (2680 Words)mentioning
confidence: 99%
“…Previously, we have shown that split GFP 1-10/11 has nearly identical overall brightness as its fulllength counterpart, whereas both split mNeonGreen2 1-10/11 (mNG2 1-10/11 ) and split sfCherry2 1-10/11 are substantially dimmer (9). This sub-optimal performance of mNG2 1-10/11 and sfCherry2 1-10/11 could be attributed to either (a) the lower molecular brightness of complemented split FPs or (b) incomplete complementation between the FP 1-10 and FP 11 fragments.…”
Section: The Complementation Efficiency Of Split Sfcherry2 and Split mentioning
confidence: 96%
“…Self-associating split fluorescent proteins (FPs) are a powerful tool for protein labeling and livecell imaging. In this system, the eleventh β-strand of FP (FP 11 , 16 amino acids) is separated out from the remainder of FP (FP [1][2][3][4][5][6][7][8][9][10] ) and is genetically fused to the protein of interest (POI).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation